Defining and Exploring the Dimensionality of ‘Halal Hotel’ Concept - Izwan Harith Md Ithnan; Nurul Nadirah Abu Hasan; Afiqah Mior Kamarulbaid; Muhammad Raqib Mohd Sofian (USIM Press, 2024)
Journal Contemporary Islamic Communication & Media Volume 2 Issue 1 Page (141-168)